Observations on Causative Verbs in Lithuanian and Russian (the Verbs of Physical Action) - Глазова, Г. С. (Kalbotyra, 1981)
This article deals with causative verbs, a variety of transitive verbs. It analyses semantical and semantical-syntactical particularities of causative verbs in the Lithuanian and Russian languages. Causative verbs of concrete physical action and causative verbs of relative physical action have been recorded.